A novel approach for development of printed circuit board from biofiber based composites - Bharath, Kurki N.; Madhu, Puttegowda; Gowda, Thyavihalli G. Y.; Verma, Akarsh; Sanjay, Mavinkere R.; Siengchin, Suchart (Polymer composites, 2020)
Over past few decades, the electronic boards density and performance are enhanced by entrenching the components in the interior surfaces of the printed circuit boards (PCBs).The worthiness of this novel innovation has to be probed to warranty the functioning of electronic boards acquiesced to callous environments. In this study, a novel advancement concentrating on the development of bio‐based materials for the PCB applications has been documented. The bio‐based composite from rice husk‐epoxy resin could impendingly substitute the conventional synthetic fiber reinforced epoxy composites in PCB applications. The essential properties of biocomposites were assessed such as tensile and bending properties, dielectric property, thermal properties, moisture absorption, microdrilling, biodegradability, and flammability. Results obtained found that, these biocomposites were promising for PCB application.